2023
DOI: 10.1186/s12935-023-02933-7
|View full text |Cite
|
Sign up to set email alerts
|

An innovative model based on N7-methylguanosine-related lncRNAs for forecasting prognosis and tumor immune landscape in bladder cancer

Abstract: Background As a novel type of the prevalent post-transcriptional modifications, N7-methylguanosine (m7G) modification is essential in the tumorigenesis, progression, and invasion of many cancers, including bladder cancer (BCa). However, the integrated roles of m7G-related lncRNAs in BCa remain undiscovered. This study aims to develop a prognostic model based on the m7G-related lncRNAs and explore its predictive value of the prognosis and anti-cancer treatment sensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…PPI network showed that FN1 and ITGB1 were the core genes in regulating m7G 125 . Similar mechanisms were demonstrated in breast cancers and bladder cancers 127 , 132 . However, it was reported in LUAD and cutaneous melanoma that neutrophils were less infiltrated in group of high m7G levels 56 , 133 .…”
Section: The Roles Of M7g Modification In Immune Cell Biologysupporting
confidence: 72%
See 2 more Smart Citations
“…PPI network showed that FN1 and ITGB1 were the core genes in regulating m7G 125 . Similar mechanisms were demonstrated in breast cancers and bladder cancers 127 , 132 . However, it was reported in LUAD and cutaneous melanoma that neutrophils were less infiltrated in group of high m7G levels 56 , 133 .…”
Section: The Roles Of M7g Modification In Immune Cell Biologysupporting
confidence: 72%
“…The prognostic models of ovarian cancers, CRC, HCC and HNSCC based on m7G regulators indicated more recruitment of M1 macrophages in low-risk group of patients 85 , 96 , 115 , 126 . However, contradictory outcomes were observed in bladder cancers 107 , 127 . In addition, as precursor cells of macrophages, monocytes infiltration was reported to be negative correlated with m7G levels in CRC, bladder cancers and prostate cancers 89 , 127 , 128 .…”
Section: The Roles Of M7g Modification In Immune Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…WWC2-AS2 has been identified as an immune-related lncRNA in cervical cancer [28]. LINC01338 is a member of N7-methylguanosine-related lncRNAs in bladder cancer [29], It can also be used to accurately predict the prognosis of bladder cancer patients, providing strong guidance for clinicians in developing better-individualized precision treatment strategies. TIDE (http://tide.dfci.harvard.edu/) stands for tumor immune dysfunction and rejection.…”
Section: Results Of In Vitro Cell Function Experimentsmentioning
confidence: 99%
“…In order to investigate how changes in eRNA expression influence prognosis, it is essential to compare the functional and signaling pathway differences between the high-risk and low-risk subgroups, which are grouped based on the 8-eRNA model [22]. We conducted a differential expression analysis between these two groups (Figure S1a,b) and identified 141 genes that were differentially expressed using the GSEA analysis thresholds of |log2FC| ≥ 1.5 and p < 0.05 (Table S5).…”
Section: Six Pathways Enriched In High-risk Populationsmentioning
confidence: 99%